Bank Stocks and the Analysis of Covariance - Durand, David (Econometrica, 1955)
THIS HIGHLY specialized paper grew out of a rather general program for analyzing security prices by multiple regression, with the ultimate objective of answering a whole series of questions regarding the supply of and demand for capital. The selection of bank stocks for immediate attention arose out of the unusual condition of bank capital following the World War II inflation, when rapid expansion of deposits was reducing the capital-to-asset ratios of banks to historically low levels. At the same time, the market for bank stocks was somewhat unfavorable, with many issues selling for less than book value, so that bankers often seemed reluctant to raise additional capital by means of new stock issues. Thus the bank stock market commanded the attentions of the bank supervisory officials and bankers alike. Were the common discounts from book value due to unsatisfactory bank earnings? If so, what level of eamings would be required to eliminate these discounts? Or could discounts be substantially reduced, if not entirely eliminated, by merely paying more generous dividends out of existing earnings? Finally, were the discounts in any way affected by capital-to-asset ratios? These questions, whose economic implications are discussed elsewhere,2 can all be attacked by a multiple regression analysis in which the dependent variable consists of bank stock prices and the independent variables consist of such quantities as book value, dividends, and earnings. But although the answers thus obtained are suggestive, and possibly provocative, there remains the haunting doubt that the rigid assumptions of regression analysis do not justify its use with bank stock prices.